In Silico Evaluation of Pharmacokinetics and Toxicity Profile of AlkaloidsPresent in Leaves of Catharanthus roseus L. - Ramgopal M Dhanwad; Usha R; Ganesh S (RGUHS Journal of Pharmaceutical Sciences)
Background Catharanthus roseus Madagascar periwinkle is a well-known medicinal plant that produces a variety of alkaloids with significant pharmacological activities particularly in cancer and diabetes treatment.Aim This study aimed to predict and analyze the pharmacokinetic and toxicological properties of major alkaloids present in the leaves of C. roseus L. using computational tools. The goal was to identify compounds with favorable drug-likeness profiles and minimal toxicological risks potentially guiding further drug development. Methodology Vincristine Vinblastine Catharanthine Vindoline Ajmalicine Vindolidine Lochnericine Serpentine and Tabersonine are the alkaloids chosen for the study. Chemical structures of the alkaloids were retrieved from ChemDraw software. Drug-likeness was assessed using Lipinskirsquos rule of five and Molsoft server. Toxicology and pharmacokinetic features were determined using the ADMETtab server.Results The study collected data on the pharmacokinetic and toxicological properties of various alkaloids along with their drug-likeness scores. Among the selected alkaloids Vinblastine showed the highest drug-likeness score. While most alkaloids showed favorable drug-like characteristics and absorption distribution metabolism and excretion ADME profiles a few demonstrated potential toxicity concerns such as mutagenicity and skin sensitization. Conclusion The current in-silico study demonstrated that computational predictions and server-based analyses were essential and informative in obtaining data on potential drug candidates their pharmacokinetics and the toxicity profiles of bioactive compounds from C. roseus L.Keywords Catharanthus roseus L Alkaloids Pharmacokinetics Toxicology Drug-likeness